قلق الموت لدى المقبلين على العملية الجراحية - وقاد, سمية; مكي, محمد (جامعة الوادي - University of Eloued, 2020)
تهدف هذه الدراسة إلى دراسة قلق الموت لدى المقبلين على العملية الجراحية، وشارك في الدراسة (205) مريض ومريضة عبر مستشفيات ولاية الوادي. لجمع بيانات الدراسة تم تطبيق مقياس قلق الموت من إعداد الباحثين. وبعد تحليل البيانات إحصائيا، أسفرت الدراسة عن النتائج الآتية: - لا توجد فروق ذات دلالة إحصائية في قلق الموت لدى المرضى المقبلين على العملية الجراحية حسب العمر. - لا توجد فروق ذات دلالة إحصائية في قلق الموت لدى المرضى المقبلين على العملية الجراحية حسب نوع العملية. - توجد فروق ذات دلالة إحصائية في قلق الموت لدى المرضى المقبلين على العملية الجراحية حسب نوع المستشفى.Abstract: This study aims to study the death stress of those who are patients about to have the surgery, Participants comprised 205 patients in the study through El oued Valley hospitals. To collect study data, a death anxiety scale was used by researchers. After analyzing the data statistically, the study yielded the following results: -There were no statistically significant differences in death anxiety in patients who were about to undergo surgery by age. -There are no statistically significant differences in death anxiety in patients who are about to undergo surgery by type of operation. -There are statistically significant differences in death anxiety in patients who are about to undergo surgery by type of hospital.
مقال
Keywords: قلق الموت؛ المريض المقبل على العملية الجراحية; death anxiety, a patient is about to have surgery